2010
DOI: 10.2176/nmc.50.1062
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Hypermethylation of Non-Promoter Zygote Arrest 1 (Zar1) in Human Brain Tumors

Abstract: Zygote arrest 1 (ZAR1) is a novel maternal-effect gene which is extremely important during the oocyteto-embryo transition. Comprehensive methylation analysis of tumor-specific differentially methylated regions in human malignant melanoma has recently led to the identification of non-promoter hypermethylation of the ZAR1 gene that had never been previously linked to aberrant methylation. Strikingly, ZAR1 hypermethylation was frequently observed in melanomas but was absent in benign nevi, and ZAR1 expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…Previously, we performed restriction landmark genomic scanning to identify novel genomic regions of mouse skin tumor-specific differentially methylated regions (DMRs), and found 14 DMRs that were highly conserved between mouse and human (2)(3)(4)(5). Among these, we focused on retinoic acid receptor-related orphan receptor α (RORA), which is frequently downregulated in CRC and is correlated with tumor progression (6).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we performed restriction landmark genomic scanning to identify novel genomic regions of mouse skin tumor-specific differentially methylated regions (DMRs), and found 14 DMRs that were highly conserved between mouse and human (2)(3)(4)(5). Among these, we focused on retinoic acid receptor-related orphan receptor α (RORA), which is frequently downregulated in CRC and is correlated with tumor progression (6).…”
Section: Introductionmentioning
confidence: 99%
“…The most widely adopted noninvasive urine test is cytology, which has good specificity and sensitivity for the detection of high-grade tumors, but poor sensitivity for low-grade tumors [13] and often takes time to generate results [14]. To discover novel markers that are more specific and sensitive in detecting bladder cancer, we examined the methylation status of ZAR1 , which has been reported to be aberrantly methylated in mouse skin tumors and human tumors such as melanoma, brain tumor, and hepatocellular carcinoma [6,7,8]. …”
Section: Discussionmentioning
confidence: 99%
“…In these analyses, CpGi in the zygote arrest 1 (ZAR1) exon 1/intron 1 was aberrantly methylated in melanoma, brain tumor, and hepatocellular carcinoma compared with normal tissues [6,7,8]. In particular, in hepatocellular carcinoma, higher methylation levels of ZAR1 exon 1/intron 1 were associated with lower serum albumin levels, which are markers of poor prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Shinojima et al noted a very high frequency of hypermethylation of the ZAR1 intergenic region in human melanomas, in contrast to non-methylation in both normal human epidermal melanocyte cell lines and melanocytic nevus surgical specimens 9) . Watanabe et al reported that hypermethylation of ZAR1 in various types of human brain tumors 25) . Seven candidate aberrantly methylated genomic regions, which have yet to be identified by whole genome scan, were analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%